Compensação de harmônicos como serviço ancilar em geração distribuída - Rocha, Jéssica Pederneiras Moraes (2017)
With the increasing integration of distributed generation in the grid, from alternative sources mainly, it was opened the possibility of using this technology to provide other services (ancillary services) to the grid in addition to active power injection. In this work, the use of an alternative photovoltaic energy source connected to the electric grid through a voltage source inverter with pulse width modulation is studied and implemented, in addition to the active power injection, to attenuate current harmonics present in the grid due to the nonlinear loads connected at the point of common coupling. One of the advantages of the proposed strategy is that the compensation is performed without the need to extract the harmonic components present in the current, which reduces the computational effort. For implementation the measured grid current is used as control variable. The control is based on the power balance in the grid and the inverter, and is carried out in the synchronous reference frame. The validation of the results was performed through simulation in PC environment using the PSIM software and experimental environment, through a platform implemented in the ‘Laboratório de Otimização de Sistemas de Energia’ - LOSE. Simulations and experiments were performed for several scenarios and the results obtained validate the control strategy used, highlighting the benefits of providing ancillary services in reducing the harmonic components present in the grid.